Analysis of the Use of Securities As an Investment Tool In the Commercial Law Code (KUHD) - Nada Adista Rambe; Aufiya Muhammad Syukri Alghiffary; Khania Amanda Salsabila; Gilang Ade Prabowo; Ahmad Asri Nasution (ISNU Sumatera Utara, 2025)
The Commercial Code (KUHD) regulates securities as an important tool in the world of trade and investment. The purpose of this article is to examine the use of securities as an investment tool based on the provisions applicable in the KUHD, which covers types of securities such as bills of exchange, checks, and bonds, and how securities are used in contemporary trade practices. This study uses normative juridical research to investigate the relationship of securities in the KUHD to current investment needs and identify legal issues encountered when using them. The results show that, although the KUHD provides a strong legal basis, regulatory changes are needed to provide legal certainty and protection for investors. To increase the competitiveness of the Indonesian capital market, this article recommends modernizing the securities system.